Orthostatic Resiliency During Successive Hypoxic, Hypoxic Orthostatic Challenge: Successful vs. Unsuccessful Cardiovascular and Oxygenation Strategies - Nordine, Michael; Treskatsch, Sascha; Habazettl, Helmut; Gunga, Hanns-Christian; Brauns, Katharins; Dosel, Petr; Petricek, Jan; Opatz, Oliver (Frontiers in Physiology, 2021)
Introduction: Rapid environmental changes, such as successive hypoxic-hypoxic orthostatic challenges (SHHOC) occur in the aerospace environment, and the ability to remain orthostatically resilient (OR) relies upon orchestration of physiological counter-responses. Counter-responses adjusting for hypoxia may conflict with orthostatic responses, and a misorchestration can lead to orthostatic intolerance (OI). The goal of this study was to pinpoint specific cardiovascular and oxygenation factors associated with OR during a simulated SHHOC. Methods: Thirty one men underwent a simulated SHHOC consisting of baseline (P0), normobaric hypoxia (Fi02 = 12%, P1), and max 60 s of hypoxic lower body negative pressure (LBNP, P2). Alongside anthropometric variables, non-invasive cardiovascular, central and peripheral tissue oxygenation parameters, were recorded. OI was defined as hemodynamic collapse during SHHOC. Comparison of anthropometric, cardiovascular, and oxygenation parameters between OR and OI was performed via Student’s t-test. Within groups, a repeated measures ANOVA test with Holm-Sidak post hoc test was performed. Performance diagnostics were performed to assess factors associated with OR/OI (sensitivity, specificity, positive predictive value PPV, and odd’s ratio OR). Results: Only 9/31 were OR, and 22/31 were OI. OR had significantly greater body mass index (BMI), weight, peripheral Sp02, longer R-R Interval (RRI) and lower heart rate (HR) at P0. During P1 OR exhibited significantly higher cardiac index (CI), stroke volume index (SVI), and lower systemic vascular resistance index (SVRI) than OI. Both groups exhibited a significant decrease in cerebral oxygenation (TOIc) with an increase in cerebral deoxygenated hemoglobin (dHbc), while the OI group showed a significant decrease in cerebral oxygenated hemoglobin (02Hbc) and peripheral oxygenation (TOIp) with an increase in peripheral deoxygenated hemoglobin (dHbp). During P2, OR maintained significantly greater CI, systolic, mean, and diastolic pressure (SAP, MAP, DAP), with a shortened RRI compared to the OI group, while central and peripheral oxygenation were not different. Body weight and BMI both showed high sensitivity (0.95), low specificity (0.33), a PPV of 0.78, with an OR of 0.92, and 0.61. P0 RRI showed a sensitivity of 0.95, specificity of 0.22, PPV 0.75, and OR of 0.99. Delta SVI had the highest performance diagnostics during P1 (sensitivity 0.91, specificity 0.44, PPV 0.79, and OR 0.8). Delta SAP had the highest overall performance diagnostics for P2 (sensitivity 0.95, specificity 0.67, PPV 0.87, and OR 0.9). Discussion: Maintaining OR during SHHOC is reliant upon greater BMI, body weight, longer RRI, and lower HR at baseline, while increasing CI and SVI, minimizing peripheral 02 utilization and decreasing SVRI during hypoxia. During hypoxic LBNP, the ability to remain OR is dependent upon maintaining SAP, via CI increases rather than SVRI. Cerebral oxygenation parameters, beyond 02Hbc during P1 did not differ between groups, suggesting that the during acute hypoxia, an increase in cerebral 02 consumption, coupled with increased peripheral 02 utilization does seem to play a role in OI risk during SHHOC. However, cardiovascular factors such as SVI are of more value in assessing OR/OI risk. The results can be used to implement effective aerospace crew physiological monitoring strategies.